Karakter Gotong Royong P5 Tahap Pengenalan dan Kontekstualisasi Tema Gaya Hidup Berkelanjutan SDN 52 Kota Bengkulu - Sakdiyah, Halimahtus; Susanti, Atika (JURIDIKDAS, 2025)
This study aims to describe the character of mutual cooperation through P5 stage of introduction and contextualization of sustainable lifestyle themes in fine arts learning in class VC SDN 52 Bengkulu City. This type of research is qualitative research with descriptive research methods. The location of this study is SDN 52 Bengkulu City. The subjects of this study were the principal, homeroom teacher VC and all students of class VC SDN 52 Bengkulu City. The research instruments were observation sheets, interview guidelines, and documentation. Data collection techniques used in this study were observation, interviews and documentation. Data analysis techniques through data collection, data reduction, data presentation and drawing conclusions. Data validity through triangulation of sources and techniques. The results of this study are the character of mutual cooperation of students through P5 which is focused on the introduction and contextualization stages. Students make flower pots that are included in the theme of sustainable lifestyles and students also help other friends to continue working on group assignments together so that students can know their roles in the group. In each stage of the implementation of P5, students are taught the importance of mutual cooperation between each other. So the conclusion obtained is that through P5 activities can strengthen the character of mutual cooperation of students. Judging from the introduction and contextualization stages, students have shown attitudes of collaboration, caring and sharing.